(3CfHGA CHfGA GdRef aj JGQjN Gdjefs - (3ESeGYjd Hf CMeO Hf Ydj Hf GdeJhcds
(3ChdgG (B:s
(3GdMeO ddg GdPi dG Edg EdG gh GdhGMO hHYO aEf GdJGQjN deG cGf eYQaJg ef LedI GdYdhe GdOjfjI hajg GdahGFO GdJi djSJ NGajI Ydi Phi GdCMdGe GdRcjI hbGd HYV GdYdeGA Ef UhQI Gdjef hGdTGe hGdYQGb s
(3BNQgG (B:s
(3GdcdGe ZjQ hGVM ai GdJUhjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs